Factors That Influence Purchase Decision in E-Commerce in Jakarta and Tangerang - Gunawan, Arby Virto; Linawati, Linawati; Pranandito, Dimas; Kartono, Rano (Binus Business Review, 2019)
This research aimed to identify the factors that influenced the purchase decision in e-commerce. These used factors were brand image, price, and trust which were adopted from the previous research. This research was based on quantitative research to test the research hypothesis and reveal the factors affecting purchase decision in e-commerce. The accidental sampling was used. From 200 questionnaires, there were 117 returned questionnaires from respondents who had made online purchases around Jakarta and Tangerang. Through the calculation using linear regression method in SPSS, the result shows that brand image has positive influences on purchase decision. On the other hand, price and trust do not influence purchase decision. Price is the level of secondary commitment to make a purchase decision. Thus, a lower price does not guarantee the convenience of online shopping. Meanwhile, trust in making online decisions are built from brand image, shop, and strong products in the market place. Those rejected variables are affected by research fields and target samples.